Narrative discourse characteristics of South African Afrikaans speaking Cape Coloureds with aphasia - Venter, Analou (Department of Health and Rehabilitation Sciences, 2017)
The spoken language production of eight Afrikaans speaking Coloured persons with mild to moderate aphasia and eight Afrikaans speaking Coloured persons without aphasia were explored using a narrative discourse analysis procedure. The aim of the study was to investigate the discourse characteristics of the Cape Afrikaans dialect in persons with and without mild to moderate aphasia. Furthermore the study aimed to establish the cultural appropriateness as well as the clinical applicability of the newly developed Discourse Test Battery (Ulatowska et al., 1998) for the Afrikaans speaking Coloured population. In addition the adaptation features as well as the dialectal and discourse ethnic markers features were identified. The narrative Discourse Test Battery devised by Ulatowska et al., (1998) consisting of two composite pictures, a picture sequence story, a story retell and personal experience task was administered to all subjects. For the purpose of investigating the higher cognitive and linguistic processes, the formulation of main ideas, providing the lessons for the stories as well as proverb interpretation tasks were included and analysed. The narrative discourse productions were transcribed and analysed using more stringent reliability measures. Measures of reliability were obtained by calculating inter-rater and intra-rater reliability measures. The data was analysed in terms of the length of narratives, pr6positional units, quality analysis, analysis of evaluation analysis of dialectal features and ethnic discourse markers as well as adaptation features. The results indicated that for all of these methods of assessment the experimental group performed poorer than the control group. Statistically significant differences were noted on the measures of expressive phonology, lexical items, global structure, suspense, clarity and temporal sequence of some of the narrative tasks. One of the most important clinical as well as theoretical findings was the overlap between some of the dialectal features, general discourse features as well as adaptation features. Analysis of the task effects indicated that the picture sequence and the personal experience narratives showed the greatest differences between the groups and revealed the most information with regard to dialectal features, discourse ethnic markers and adaptation features. The spontaneous proverb and multiple choice proverb interpretation tasks revealed greater difficulties in abstracting and generalising information for the experimental group than for the control group. The assessment tool was found to be culturally appropriate for the Afrikaans speaking Coloured population of the Western Cape.